SINERGI POLISI DAN MASYARAKAT DALAM MEMBANGUN KETAHANAN REMAJA TERHADAP NARKOBA DAN JUDI ONLINE - Sigit, Andik Purnomo; Torrido, Aryan (The Juris, 2024)
This study aims to examine the importance of synergy between the police and the community in preventing drug abuse and online gambling in Indonesia. Drug abuse and online gambling are serious threats to public security and health, especially among adolescents. This study uses a qualitative approach with a normative juridical method, where data is collected through literature studies that include books, journals, and reports related to the prevention of drug abuse and online gambling. This research emphasizes the importance of collaboration between law enforcement and the community as both preventive and repressive efforts in addressing these issues. The results of the study show that the synergy between the police and the community can enhance the effectiveness of preventing and tackling drug abuse and online gambling. The police play a role in providing socialization, counseling, and taking firm actions against legal violations, while the community acts as the frontline in early detection and reporting of cases. Collaborative programs such as anti-drug campaigns, community forums, and reporting apps contribute significantly to reducing the rates of drug abuse and online gambling. This study also suggests that to improve the success of prevention and intervention efforts, there is a need for policies that strengthen cooperation between the police, community organizations, and the government, as well as the development of more inclusive rehabilitation systems. The implementation of this synergy is expected to create a safer environment free from the threats of drug abuse and online gambling, especially for the younger generation in Indonesia.